Jord i portföljen - Danielsson, Viktor (2011)
People who invest capital in promising projects as a profession are called venture capitalists. They are constantly looking for new investment opportunities. Recently, media have observed a growing interest in forest land as capital investment. This is because several fund and investment company market the possibility of safe return through investment in woodland, both in Sweden and abroad. When an investment in forests is seen as an acceptable investment option, focus turns to nearby areas, namely agricultural land. Over the last 15 years, the average price of Swedish agricultural land has more than quadrupled.